The ethical dimensions of Mong Kinemong in music performance in catholic worship: a phenomenological analysis of first Friday night eucharist musicians at Ganjuran Church - Rosidy, Tony Anwar; Rustandi Mulyana, Aton; Suryo Prabandari, Yayi (Pascasarjana Institut Seni Indonesia Surakarta, 2023)
In the context of Catholic worship at Ganjuran Church, music and musicians play vital roles in enhancing the spiritual experience of worshippers. This research employs a qualitative and phenomenological approach to explore the ethical aspects related to musical performances during the First Friday Night Eucharist. Through careful observation, interviews, and documentation, the study analyzes the musicians' practices using Marc Benamou's theory of Rasa and Keontjoroningrat's insights on religious emotion. The findings reveal that musicians at Ganjuran Church embody the ethical principle of 'Mong Kinemong,' demonstrating a profound ethos of mutual care deeply embedded in their musical practice. This ethical commitment is bolstered by the musicians' intense experience of religious emotion, evoking feelings of majesty and serenity among choir members. Additionally, instrumentalists, referred to as 'pengrawit,' express heightened veneration, describing their peak moments as 'semu' (joyful), 'nges' (serene and good), and 'dados' (fulfilling expectations). Importantly, this 'Mong Kinemong' ethos harmoniously integrates with musical elements, enhancing the overall worship experience. This study contributes to a deeper understanding of ethics in musical performance within the Catholic liturgy context, shedding light on the significance of mutual care, emotional resonance, and harmonious musical expression in enriching the spiritual dimension of worship.